2013
DOI: 10.1088/0960-1317/23/10/105016
|View full text |Cite
|
Sign up to set email alerts
|

Influences of pretreatment and hard baking on the mechanical reliability of SU-8 microstructures

Abstract: In this paper, the influences of pretreatment and hard baking on the mechanical characteristics of SU-8 microstructures are described. Four types of samples with different combinations of O2 plasma ashing, primer coating and hard baking were prepared for shear strength tests and uniaxial tensile tests. Specially developed shear test equipment was used to experimentally measure the shear adhesion strength of SU-8 micro posts on a glass substrate. The adhesiveness was strengthened by hard baking at 200 °C for 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…This implies that some ether groups decomposed into the carbonyl group during the heat treatment 18 . The polymer crosslinking could also be directly proven by the enhancement of mechanical strength 25 . The elastic modulus and the hardness of the SU8 nanopatterns were measured via nanoindentation, as shown in Figure S4 .…”
Section: Resultsmentioning
confidence: 99%
“…This implies that some ether groups decomposed into the carbonyl group during the heat treatment 18 . The polymer crosslinking could also be directly proven by the enhancement of mechanical strength 25 . The elastic modulus and the hardness of the SU8 nanopatterns were measured via nanoindentation, as shown in Figure S4 .…”
Section: Resultsmentioning
confidence: 99%
“…This new nanocomposite method has proven useful for enhancing various physical and chemical properties of polymers, including mechanical strength. , We applied the infiltration synthesis of aluminum oxide (AlO x ) to polymer nanopillars lithographically patterned from a commercial epoxy-based resist SU-8 . Designed for negative-tone (i.e., cross-linkable) lithographic patterning and being one of the strongest polymeric materials (σ y ∼ 60 MPa) with moderate E (∼2–4 GPa), , SU-8 is the primary polymer system utilized extensively for MEMS/NEMS applications. , Thus, our nanopillar was made using conventional MEMS fabrication techniques and its dimension and material properties are similar to those of typical MEMS SU-8 components.…”
mentioning
confidence: 99%
“…With the coating of the adhesive promoter, which is 100 wt% hexamethyldisilazane (Tokyo Ohka Kogyo Co., Ltd; OAP) and enables the reduction of the SU-8 polymer chains breakage, SU-8 would exhibit higher yield strength and higher tensile strength in primer-coated tensile specimens. 4 Wouters and Puers found that the SU-8 epoxy will swell on being immersed in a solution because of the absorption or desorption of water to result in the volume change, or alternatively a change in built-in stress. 5 In addition, experimental results showed the built-in stress of SU-8 reached its maximum value when submersed in propylene glycol methyl ether acetate and in isopropyl alcohol and the stress will be strongly correlated with the formation of cracks and delamination in SU-8.…”
Section: Microfabrication Processesmentioning
confidence: 99%